PENERAPAN "INSPIRA" INKUBATOR INOVASI PRIMA DALAM MENYELESAIKAN MASALAH PELAYANAN DI RSUD SIDOARJO BARAT - Nurdianto, Arif Rahman (Jurnal SADEWA, 2025)
Indonesia's innovation index is low, presenting a challenge for healthcare services like RSUD Sidoarjo Barat, which faces issues with staff problem-solving skills and innovation motivation, leading to a decline in innovation output. This community service activity aimed to accelerate problem-solving and foster innovation through the establishment and implementation of the Prima Innovation Incubator at RSUD Sidoarjo Barat (INSPIRA). The activity involved structured steps including problem identification, analysis, solution development, and INSPIRA implementation with training and a digital platform in selected units. Results showed a significant increase in staff understanding (pre-post test scores) and a substantial rise in the number of innovations generated (from 4 to 16, a 300% increase). The INSPIRA program successfully transformed staff mindset and empowered them to generate new solutions. In conclusion, INSPIRA is an effective breakthrough addressing innovation challenges, significantly increasing innovation capacity and contributing to service improvement